How Tax Consultants and E-Commerce Actors Grapple with Evolving Digital Tax Rules - Juliansah, Irvan; Marthalina (prodima@fe.uika-bogor.ac.id, 2025)
The rapid growth of Indonesia's digital economy has created challenges for tax collection, prompting new regulations. This study explores the on-the-ground effectiveness of these digital tax rules. A qualitative case study was conducted in Greater Jakarta, using interviews and observations with e-commerce actors and tax consultants. Data were analyzed thematically. The implementation is hampered by regulatory complexity, low tax literacy, and technological limitations. Perceptions of fairness strongly influence voluntary compliance, while tax consultants act as essential intermediaries who bridge the gap between regulators and taxpayers. The study advocates for simplified regulations, improved taxpayer education, and robust infrastructure support to enhance compliance and foster a more effective digital taxation system.